2011
DOI: 10.1111/j.2042-3292.2011.00336.x
|View full text |Cite
|
Sign up to set email alerts
|

Distichiasis causing recurrent corneal ulceration in two Friesian horses

Abstract: Summary Two cases of distichiasis with subsequent recurrent superficial corneal ulceration are described in Friesian horses. Case 1 was a 9‐year‐old Friesian stallion with distichiae on the superior and inferior eyelids of both eyes corresponding to areas of recurrent superficial corneal ulceration. Case 2 was a 5‐year‐old Friesian gelding with a single distichia on the inferior lid associated with recurrent superficial corneal ulceration in the right eye. Case 1 underwent cryotherapy and epilation twice under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Distichiae are a differential for corneal ulceration in the horse, particular in the Friesian breed . This case series supports this statement, revealing a predisposition for distichiasis in the Friesian breed, as 17 out of 18 horses presented with this condition were Friesians (94%), whereas Friesians comprise only 7% of the general hospital population .…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Distichiae are a differential for corneal ulceration in the horse, particular in the Friesian breed . This case series supports this statement, revealing a predisposition for distichiasis in the Friesian breed, as 17 out of 18 horses presented with this condition were Friesians (94%), whereas Friesians comprise only 7% of the general hospital population .…”
Section: Discussionsupporting
confidence: 77%
“…Recently, 2 cases of distichiasis in Friesian horses have been described, suggesting the possibility of a breed predisposition . In the current report we describe 18 cases of distichiasis in the horse over a period of 9 years, causing recurrent corneal irritation and/or superficial corneal ulceration and provide details of electrocautery treatment with long‐term follow‐up.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In the case series in this issue by Utter and Wotman (2012), 2 Friesian horses had chronic or recurrent superficial corneal ulceration and diagnostic testing was performed as described above. Distichia was observed that directly contacted the ulcerated area of the cornea.…”
Section: Clinical Commentarymentioning
confidence: 99%
“…This author has observed a few cases of distichia and ecotopic cilia in Thoroughbreds and therefore these conditions may be underreported in other breeds. Because of the recurrent nature of distichia as reported in the Friesian horses (Utter and Wotman 2012), more studies of the pathogenesis and treatment of distichiasis in horse are also needed.…”
Section: Clinical Commentarymentioning
confidence: 99%